Fluorides in the ground waters of Amravati district (M.S), India - Kakde, A U; Tarar, J L; Ingole, S P (International Multidisciplinary Research Journal, 2012)
India is one of the important country on the world map and ranks 3rd for its water reservoirs. Although it is blessed with these reservoirs ground water constitutes the main reliable source for drinking water. The concentration of elements is of great concern. Keeping in mind the dilema of fluoride and its impact the present study carried out for Amravati district where major portion of population rely on the ground water source. Consumption of excessive fluorides in drinking water causes dental decay and physiological deformities. In the present study it is observed that some glimpses of Nimbhi and Daryapur are above the prescribed limits. A variation in concentration is seen with the change in season. Some spots like Mullapua, Amravati are approaching the verge of contamination. Need for continuos and recurrent monitoring of water will be helpful for betterment.Â